A case of hereditary sensory autonomic neuropathy type IV - Prashanth, G. P. (Medknow Publications & Media Pvt Ltd, 2012)
Hereditary sensory autonomic neuropathy type IV (HSAN -IV), also known as congenital insensitivity to pain with anhidrosis, is a very rare condition that presents in infancy with anhidrosis, absence of pain sensation and self -mutilation. Developmental delay and mental retardation are usually present. Ultrastructural study of the peripheral nerves demonstrates loss of the unmyelinated and small myelinated fibers. We here report a 8 year -old boy with HSAN IV with typical clinical features where the diagnosis was supported by nerve biopsy findings. However, our case was unusual since mental development was normal.